2009
DOI: 10.1007/s11055-009-9189-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlational Relationships Between the Hippocampus and Medial Septal Area and Their Changes During Epileptogenesis

Abstract: EEG traces were recorded from the hippocampus and medial septal area of conscious guinea pigs in control conditions and on repeated stimulation of the perforant path. Changes in the correlations of activity in these structures during stimulation-evoked convulsions (a model of acute epilepsy) and during the process of epileptogenesis (a model of chronic epilepsy) were analyzed. A high correlation between baseline activity in the hippocampus and medial septal area seen in control conditions decreased sharply wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…This would require temporally aligned stimulus delivery targeting specific phases of pathological oscillations (Berényi et al, 2012;Dejean et al, 2016;Kozák and Berényi, 2017). Because of its direct reciprocal connections, the septohippocampal axis resonates in a highly coherent manner in both physiological and pathophysiological conditions, including ictal periods of epilepsy (Sinel'nikova et al, 2009;Tsanov, 2018). The stimulation of medial septum neurons can precisely entrain HPC local field potentials (LFPs) (Fuhrmann et al, 2015;Robinson et al, 2016;Zutshi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This would require temporally aligned stimulus delivery targeting specific phases of pathological oscillations (Berényi et al, 2012;Dejean et al, 2016;Kozák and Berényi, 2017). Because of its direct reciprocal connections, the septohippocampal axis resonates in a highly coherent manner in both physiological and pathophysiological conditions, including ictal periods of epilepsy (Sinel'nikova et al, 2009;Tsanov, 2018). The stimulation of medial septum neurons can precisely entrain HPC local field potentials (LFPs) (Fuhrmann et al, 2015;Robinson et al, 2016;Zutshi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The MS and HPC are highly coherent in both physiological and pathophysiological conditions. The electrical or optogenetical stimulation of the MS is transmitted to the bilateral HPC at exactly the same frequency that is applied within the delta to gamma-band range (Sinel'nikova et al, 2009;Zutshi et al, 2018). For human application, the thalamic stimulation for refractory epilepsy, the fornical stimulation for AD, and the medial forebrain bundle stimulation for depression all utilize this principle for DBS (Dandekar et al, 2018;Li and Cook, 2018;Mirzadeh et al, 2016).…”
Section: How To Effectively Introduce or Disturb Oscillatory Activitiesmentioning
confidence: 99%
“…In addition, the stimulation of the MS is effective to modulate oscillations in the limbic system. For example, studies showed that electrical and optogenetic stimulation of the MS is robustly transmitted to the HPC at the same frequency that is applied within the delta to gamma frequency bands (Sinel'nikova et al, 2009;Zutshi et al, 2018;Takeuchi et al, 2021). Earlier study of the MS stimulation in humans in 1950 reported a high complication rate, but it was likely related to the inexperience of the teams with depth electrode placement (Baumeister, 2000;Fisher, 2015).…”
Section: The Medial Septum As a Target For Deep Brain Stimulation For Epilepsy Control And Beyondmentioning
confidence: 99%